Effect of Incubation in NaCl Hypertonic Solutions on Changes of Adrenocorticocytes’ Volume and Arrangement of Lipid Droplets - Yurchuk, T. A.; Chernobay, N. A.; Bozhok, G. A.; Kovalenko, I. F.; Bondarenko, T. P.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2010)
Volumetric changes of cells and adrenocorticocytes’ (AC) intracellular space, within the range of which lipid droplets (LD) located, after the effect of NaCl hypertonic solutions were studied by the fluorescence and light microscopy. Under re-hydration after effect of 0.75 and 1M NaCl solutions the cell volume recovered in average up to 85% of the initial one during 20 min, and the volume of the space, occupied with LD increased up to 77 and 80%, correspondingly, i. e. the delayed recovery of space, occupied with LD and AC was observed. It is suggested that approaching of LD (depot of cholesterol) to the site of hormone synthesis due to volumetric changes of AC results in the increase of basal steroidogenesis rate after hypertonic effect.